An Interesting Case of Bilateral Facial Palsy due to Granulomatosis with Polyangiitis - Shil, Rajish Sanjit Kumar; Teir, Jamal Ali (Case Reports in Rheumatology, 2021)
Granulomatosis with polyangiitis (formerly called Wegener’s granulomatosis) is a systemic autoimmune disease, which can lead to necrotizing vasculitis affecting small vessels and cause inflammation of blood vessels in the nose, sinuses, throat, lungs, and kidneys. In rare instances, it has shown involvement of the brain and cranial nerves as well. We are reporting a case of granulomatosis with polyangiitis, complicated by bilateral facial palsy due to lower motor neuron involvement of the facial nerve, which has responded well to immunosuppressive treatment, particularly rituximab. It is prudent to be vigilant in investigating patients with atypical presentation for systemic autoimmune diseases, as this approach would affect the patient morbidity and mortality with early initiation of treatment for the disease.